(untitled) (Research, Society and Development, 2021)
Dental erosion is a chronic process characterized by chemical dissolution of the tooth surface due to the action of acids of intrinsic extrinsic or idiopathic origin. It is estimated that this condition affects about 30-50% of primary dentition and 20-45% of permanent teeth worldwide. This work aimed to report a clinical case of moderate dental erosion associated with a high intake of acidic and fermented foods. Male patient, Caucasian, 8 years old, attended the Pediatric Dentistry Clinic of Araçatuba Dental School for preventive consultation. During the anamnesis, there was consumption of soft drinks twice a week, acidic fruit juice twice a day, and a sugary milk drink once a day. On clinical examination, the absence of carious lesions, healthy gingival tissue were observed. However, there was the presence of generalized fluorosis and generalized erosive tooth wear, with characteristics such as excessive shine, smoothness, and cupping-type lesions on the occlusal surface of the primary molars, in addition, to wear on the incisor edges of incisors and canines. The immediate clinical approach involved guidance on diet and hygiene to those responsible, emphasizing the causal factors and the irreversible character of erosive tooth wear. Four sessions of topical application of fluoride varnish were carried out. Child dental care and early diagnosis of tooth wear are of paramount importance to minimize structural damage to primary teeth and prevent damage to permanent dentition.